2010
DOI: 10.1007/s00216-010-3505-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of additives in poly(vinylacetate) artist’s paints using PY-GC-MS

Abstract: Commercial poly(vinyl acetate) (PVAc) paint formulations for artists include a number of compounds in addition to the PVAc polymer and pigments to improve the physical and chemical properties of the resulting product. Among the most common additives are surfactants, coalescing agents, defoamers, freeze-thaw agents and thickeners. These products significantly influence the behaviour of the dried film. Nevertheless, they are usually difficult to detect with conventional analytical methods given their low concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 26 publications
2
36
0
Order By: Relevance
“…1b shows a series of peaks throughout the pyrogram of Conrayt ® , which correspond to POE fragments in their trimethylsilylated (TMS) form, with characteristic m/z 45, 73, 101, 103, 145 and 161. Such fragments have not been detected by conventional Py-GC-MS and can be ascribed to a diversity of additives, especially to surfactants [11]. Ethanoic acid in its TMS form can be found as a sharp peak at early retention times, which confirms the presence of the PVAc resin.…”
Section: Analysis Of Pvac Dispersion and Paintsmentioning
confidence: 88%
See 4 more Smart Citations
“…1b shows a series of peaks throughout the pyrogram of Conrayt ® , which correspond to POE fragments in their trimethylsilylated (TMS) form, with characteristic m/z 45, 73, 101, 103, 145 and 161. Such fragments have not been detected by conventional Py-GC-MS and can be ascribed to a diversity of additives, especially to surfactants [11]. Ethanoic acid in its TMS form can be found as a sharp peak at early retention times, which confirms the presence of the PVAc resin.…”
Section: Analysis Of Pvac Dispersion and Paintsmentioning
confidence: 88%
“…Py-silylation-GC-MS of VeoVa monomer produces a variety of fatty acids, which appear in their TMS form. A detailed study of these structures can be found in a previous report performed by the authors [11].…”
Section: Analysis Of Pvac Dispersion and Paintsmentioning
confidence: 96%
See 3 more Smart Citations